Public service logic : creating value for public service users, citizens, and society through public service delivery - Osborne, Stephen P., 1953- (New York, NY : Routledge, 2021)
"Public Service Logic offers a ground-breaking approach to the delivery and management of public services. For the first time, it integrates insights both from public administration and management and from service management and marketing to offer this new approach. Previous models of public administration and management (such as the New Public Management) have been focused either upon the internal efficiency of public service organizations or upon how to 'add-in' citizens to public service delivery through co-production. This book offers a new approach with three core elements. First, it understands public services as 'services' with a service-dominant rather than product-dominant orientation. Second, it focuses upon adding external value to citizens and public service users rather than simply upon the internal efficiency of public service organizations. Third, it offers a coherent model of the nature and dimensions of 'value' in relation to public services and how it can be created (or destroyed) through public services delivery. Public Service Logic will be of interest to researchers and students in the fields of public management and public administration, as well as to policy makers and public service managers"--
OCLC-licensed vendor bibliographic record.
Keywords: Public administration; Administrative agencies -- Management; Organizational effectiveness; BUSINESS & ECONOMICS / Management; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Public Policy / Social Policy